24 Initial oxidation of LDL by iron at lysosomal pH is due to tryptophan radicals and is not inhibited by probucol. (17th November 2015) - Ahmad, F; Leake, DS
Abstract : The LDL oxidation hypothesis proposes that LDL is oxidised in arterial interstitial fluid and macrophages take it up rapidly, becoming foam cells. LDL oxidation is inhibited by interstitial fluid and large clinical trials have shown no protection by antioxidants, including probucol. We therefore proposed that LDL might be nonoxidatively modified and aggregated by enzymes in interstitial fluid, rapidly phagocytosed by macrophages and oxidised by iron inside lysosomes, which have a pH of about 4.5. We investigated the mechanisms of LDL oxidation by iron at lysosomal pH. LDL (50 µg LDL protein/ml) was oxidised by FeSO4 or FeCl3 (5 µM) at 37°C in 150 mM NaCl/10 mM sodium acetate buffer, pH 4.5. Lipid oxidation was measured in terms of conjugated dienes at 234 nm and tryptophan oxidation by the loss of fluorescence (Ex/Em 282/331 nm). Interestingly, probucol did not inhibit lipid oxidation for about 100 min for Fe2+ and Cu2+ at pH 4.5 and did not decrease the loss of tryptophan fluorescence. As probucol was unable to prevent loss of tryptophan fluorescence, but would be expected to scavenge lipid radicals, the initial oxidation of LDL at pH 4.5 might be due to the formation of tryptophan radicals which attack the lipids. We propose the following mechanism of LDL oxidation by Fe2+ at lysosomal pH. Fe2+ + O2 → Fe3+ + O2●- O2●- + H+ ↔ HO2● (pKa 4.8) HO2● + TrpH → Trp● + H2O2 Trp● + O2 → TrpOO● LH + TrpOO● → L● + TrpOOH.